Pathomorphology of Coccidiosis (Eimeria dunsingi) in a Chatter of Budgerigars - R. Saahithya; B. Prakash Krishna; S. Jaisree; G. Balakrishnan; C. Soundararajan; A. Shanmugasundaram (The Indian Veterinary Journal, 2024)
Six budgerigars (Melopsittacus undulatus) from an organised farm were presented for postmortem examination with a history of sudden mortality. Postmortem examination revealed poor carcass condition with brown pasty contents adhered around the vent. Visible mucous membranes were pale. Internal examination revealed diffuse congestion of heart, lungs, liver, kidney and spleen. The crop was empty. Entire length of the intestine revealed mild ballooning with presence of brown coloured contents in the lumen. The mucosa was highly congested. The intestinal contents were scraped and wet mount examination was performed. Microscopically, numerous unsporulated ovoid colorless oocysts without micropyle were observed which were suggestive of Eimeria dunsingi. Histopathological examination of the intestine confirmed the presence of various stages of Eimeria dunsingi within the villi and adjacent to the crypts. There were multifocal haemorrhages in the lamina propria with desquamation of villi and presence of numerous mononuclear inflammatory cells. The case was confirmed as Coccidiosis and relevant treatment was advised to the farm.